Impacts of family structure on shadow education and educational achievement among South Korean youth. (March 2022) - Jarvis, Jonathan A.; Read, Amy R.; Dufur, Mikaela J.; Pribesh, Shana
Abstract: Research examining the impact of family structure on educational achievement often overlooks differences in non-Western countries, where patterns of family formation and disruption are different, and educational pursuits are more intense. Using the Korean Youth Panel Survey, we examine the impact of family structure and shadow education on educational achievement in South Korea. While traditional resources explain much of the variation in shadow education use, family structure is also associated with the use of shadow education. Students in non-traditional families not only use shadow education less frequently, but their ability to translate shadow education into college entrance exam success also differs. Highlights: Math shadow education is associated with College Entrance Exam scores. Family structure is associated with student use of math shadow education. Like in the West, resources largely explain college entrance exam performance. Income does not increase use of math shadow education for students in single-parent families. Math shadow education does not increase College Entrance Exam scores in unstably married families